STUDY OF THE INFLUENCE Of ONLINE MOTORCYCLE TAXIS ON JOB OPPORTUNITIES FOR THE PEOPLE OF THE CITY OF PALANGKA RAYA - Setiawan, Herunur; Tarita Aprilani Sitinjak (Jurusan Pendidikan Teknologi Dan Kejuruan, 2025)
Online motorcycle taxis are application-based motorcycle taxis. Online motorcycle taxis have an impact on job opportunities. The research method used is a quantitative descriptive method. The research was conducted by distributing questionnaires to the general public. The purpose of this study was to determine the effect of online motorcycle taxis on job opportunities for the people of the city of Palangkaraya. In this study, data collection was in the form of a questionnaire which was then distributed to 100 respondents, namely the general public. The results of the questionnaire were processed using SPSS version 26 with simple linear regression analysis. The results can be proven from the results of calculations using the SPSS application version 26 on the value of the F test and t test where the results of the F test are F count (170.451) > F table (3.94) and the value of the t test value t count (13.056) > t table (1.98447). Shows that the presence of jobs using the online transportation system is an alternative to increasing people's income, especially for online motorcycle taxis because it has opened up new jobs in the City of Palangka Raya which has a good impact on increasing the income of people who previously did not have jobs